ANALISA KELAYAKAN EKONOMI PEMBANGUNAN KOLAM RETENSI SEMATANG BORANG KOTA PALEMBANG - Yunan Hamdani (UNIVERSITAS INDO GLOBAL MANDIRI, 2018)
One function of the retention pond is to replace the role of the farm absorption, which covered land / housing /office space. To accommodate the volume of water runoff from the drainage system in the area of Sematang Borang sunburn the increasingly populous required the construction of a pool of retention. Analysis on the study of economic feasibility analysis method with an indicator of Net Present Value (NPV) of the current benefits and costs, and Net Benefit Cost Ratio (Net B/C Ratio) to find out the feasibility of this retention pond construction project. From the results of the analysis note that the results of the Net Present Value (NPV) for the construction of retention ponds of Sematang Borang area is the NPV of Rp,85,-389.098.758 and the Benefit cost ratio (BCR = 1,09) with interest rate (i) 12%.Keywords : feasibility, Net Present Value (NPV), the Net Benefit Cost Ratio (Net B/C Ratio).